2013
DOI: 10.1111/mec.12328
|View full text |Cite
|
Sign up to set email alerts
|

The impact of paternity on male–infant association in a primate with low paternity certainty

Abstract: In multi-male groups where females mate promiscuously, male-infant associations have rarely been studied. However, recent studies have shown that males selectively support their offspring during agonistic conflicts with other juveniles and that father’s presence accelerates offspring maturation. Furthermore, it was shown that males invest in unrelated infants to enhance future mating success with the infant’s mother. Hence, infant care might provide fitness gain for males. Here we investigate male-infant assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
67
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(69 citation statements)
references
References 77 publications
2
67
0
Order By: Relevance
“…Also missing is information on whether aging males support their sons when they meet again in a group, as this is known from father–offspring affiliations in the natal group of the offspring (Langos et al. 2013). To assess this, we need both experiments and studies with a large number of groups, and genetically identified well‐studied individuals with known pedigrees under long‐term behavioral observation.…”
Section: Discussionmentioning
confidence: 99%
“…Also missing is information on whether aging males support their sons when they meet again in a group, as this is known from father–offspring affiliations in the natal group of the offspring (Langos et al. 2013). To assess this, we need both experiments and studies with a large number of groups, and genetically identified well‐studied individuals with known pedigrees under long‐term behavioral observation.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, spatial proximity may also be a cue that infants use to detect which adult males are their fathers. Evidence for father-offspring kin recognition has been documented in savannah baboons (Buchan et al, 2003;Onyango et al, 2012), chacma baboons (Huchard et al, 2010(Huchard et al, , 2013, rhesus macaques (Langos et al, 2013), chimpanzees (Lehmann et al, 2006), and capuchin monkeys (Muniz et al, 2006(Muniz et al, , 2010. Additionally, paternal recognition and affiliative bias of fathers toward their own offspring may also lead paternal siblings to spend more time near each other because of mutual attraction to the same adult male.…”
mentioning
confidence: 99%
“…Reports of primate studies utilizing feces have become more and more prevalent in recent years (Buchan et al 2003, Liu et al 2008, Bergman et al 2008, Langos et al 2013, Liu et al 2013. Among various molecular markers, microsatellites have been demonstrated to be ideal for analyses of genotyping, parentage, and pedigree (Estoup et al 1998, Constable et al 2001, Balloux and Lugon-Moulin 2002, Luna-González et al 2012, Charpentier et al 2012, Yang et al 2014.…”
Section: Introductionmentioning
confidence: 99%
“…Although rare, paternal care (e.g., male-infant affiliation and the selective support of offspring in agonistic interactions) in many cercopithecine species have been documented (Buchan et al 2003, Fernandez-Duque et al 2009, Langos et al 2013). Multiple-mating by promiscuous females, however, masks paternity certainty (Soulsbury 2010), which consequently could obscure the true paternal care (Buchan et al 2003, Widdig 2007.…”
Section: Introductionmentioning
confidence: 99%